Systemic Sclerosis–associated Interstitial Lung Disease at 2 Tertiary Centers in the USA and Greece: A Comparative Study of Demographics, Management, and Radiologic Progression - Nikolaos Koletsos; Amit Syal; Nafsika Gerolymatou; Meryem Nursoy; Nikolaos Zintziovas; Konstantinos Parperis; Paraskevi V. Voulgari; Chris T. Derk (JCR: Journal of Clinical Rheumatology, 2026)
Objective: To compare demographics, clinical features, treatment approaches, and outcomes of patients with systemic sclerosis-interstitial lung disease (SSc-ILD) at 2 geographically distinct tertiary centers: the University of Pennsylvania (UPenn), USA, and the University of Ioannina (UOI), Greece. Methods: A cohort of 789 SSc patients (2013 ACR/EULAR criteria) was evaluated through medical records review at both institutions. Patients initially diagnosed with SSc-ILD between January 2020 and December 2024 with at least 72 weeks of follow-up were included. Sociodemographic, clinical, serological, and treatment data were systematically collected. ILD progression was defined as radiographic worsening on serial HRCT—comprising new or increased ground-glass opacification, reticulation, or traction bronchiectasis—as assessed at each center. PFTs were obtained at baseline and at 24, 48, and 72 weeks. Results: Sixty-six patients were included (35 UPenn, 31 UOI). Arthritis (32.3% vs. 11.4%) and anti-Scl-70 positivity (64.5% vs. 40.0%) were more frequent at UOI. UOI patients had higher rates of rituximab (35.5% vs. 5.7%) and corticosteroid use (77.4% vs. 42.9%). ILD progression at 48 weeks was significantly greater in UPenn (57.1% vs. 17.2%, p